2015 IEEE International Symposium on Technology and Society (ISTAS) 2015
DOI: 10.1109/istas.2015.7439402
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mismatch between mobile phone adoption and use through survey data from rural India and China

Abstract: Persistent disciplinary and methodological divides between technology diffusion and adoption studies and the study of use and engagement with technology raise obstacles to understanding the development implications of mobile technology diffusion, for example in the area of healthcare access. As quantitative assessments in the area of health and technology almost exclusively rely on binary indicators of mobile phone adoption, it is not clear whether this is indeed a reasonable proxy that does not obscure the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This variable is calculated as the populationweighted percentage of households who own a mobile phone. In addition, the IDHS data does not include patients' healthcare-related mobile phone use, but previous research has found that the absence of household mobile phones predicts the absence of phone-aided healthcare-seeking better than the absence personal phone ownership (Haenssgen, 2015a). I therefore use household-level mobile phone ownership to approximate the likelihood of household members to engage in health-related phone use.…”
Section: Equity Implications Of Phone-aided Health Actionmentioning
confidence: 99%
“…This variable is calculated as the populationweighted percentage of households who own a mobile phone. In addition, the IDHS data does not include patients' healthcare-related mobile phone use, but previous research has found that the absence of household mobile phones predicts the absence of phone-aided healthcare-seeking better than the absence personal phone ownership (Haenssgen, 2015a). I therefore use household-level mobile phone ownership to approximate the likelihood of household members to engage in health-related phone use.…”
Section: Equity Implications Of Phone-aided Health Actionmentioning
confidence: 99%
“…Thirdly, my phone utilisation index was only a partial representation of a multidimensional concept of "adopting" mobile technology. The index focused on general yet basic functional engagement with mobile phones, which ignores specific uses like social, economic, or healthcare applications of the phone (for examples of healthcare uses, see Haenssgen, 2015aHaenssgen, , 2018Haenssgen & Ariana, 2017), and it did not include symbolic forms of engagement that could be of interest in sociological research (Lee et al, 2012). The quantitative findings were therefore shaped by my construction of the utilisation variables, which exceeded variation contained in common binary indicators of mobile phone adoption.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, Utilisationi is the respondent's mobile phone use, measured through a multidimensional and decomposable utilisation index that goes beyond conventional adoption measures and represents different manifestations of mobile phone use (Haenssgen, 2015a). As described in Appendix Table 2, the aggregate index ranges from 0 to 1 and measures the extent to which six different mobile phone functions were used directly or indirectly by the respondent in the past year (0 corresponding to less than monthly use of any function or "minimal utilisation"; 1 corresponding to daily use of all six functions or "full utilisation").…”
Section: Methodsmentioning
confidence: 99%
“… 25 30 The social dimension of precarity was evaluated through the (3) absence of other adults in the households and (4) the lack of a health-related social network (in terms of regular exchange of health advice 38 64 65 ). Lastly, logistical indicators comprised the absence of solutions to flexibly address health problems, namely (5) no household mobile phone (as consistent predictor of individual non-use of mobile phones during an illness 66 ) and (6) no motor transport option within the household (including motorcycles/tricycles, cars or tractors).…”
Section: Methodsmentioning
confidence: 99%